Pengembangan Aplikasi Monitoring Perkembangan Janin Berbasis Website - Imaduddin, Zaki; Ariyanto, Arif; Khoiron, Faiz (LPPM STT Terpadu Nurul Fikri, 2021)
Monitoring the developing fetus will make it easier to detect any abnormal symptoms of fetus growth. Monitoring is done by measuring and estimating the age and weight of the fetus. Average fetal weight at a certain gestational age refers to pregnancy statistics. A fetus that is too big or too small can cause severe problems for the delivery process and the baby's development. The process of monitoring the estimated age and weight of the fetus can do by measuring up to bids of the fundus. In order to facilitate the process of monitoring and providing information for pregnant women in graphic form, an information system that can be accessed easily is needed. A system that records fetal development and provides easy-to-understand information about fetal development for pregnant women: therefore, the development of fetal development monitoring applications is essential. Therefore the development of the fetal development monitoring app became important. It is hoped that pregnant women will find it easy to record and monitor fetal development with a fetal development monitoring application. A method for measuring the development of fetal weight do by using fetal biometric measurements through uteri height. The developed applications also provide accessible graphic information regarding the development of the fetus.